2018
DOI: 10.1128/jvi.00252-18
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Chaumorcel et al., “The Human Cytomegalovirus Protein TRS1 Inhibits Autophagy via Its Interaction with Beclin 1”

Abstract: Page 2575, Fig. 2A: Due to an error in figure file processing, the Western blots did not have the correct actin loading controls in the lower panel. All of the original films have been retrieved, and the corresponding actin loading controls have been replaced. Figure 2A should appear as shown below. This panel has a space between the blots for mock conditions and those for supernatant conditions (as in the original Fig. 2A), since the lanes were not adjacent in the original immunoblot. Page 2575, Fig. 2A, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dysregulating the activation of pathways involved in the autophagy induction, such as PKR/EIF2 alpha and mTOR, is another strategy put in place by other viruses belonging to the Herpesvirus family, such as Herpes Simplex virus-1 (HSV-1) or cytomegalovirus (HCMV) [31]. The latter, similarly to EBV, is able to promote the initial autophagic phases and inhibit the last ones, as its protein TRS1 interact with Beclin 1 [32]. As for HHV-6, EBV infection also reduces autophagy in infected monocytes, leading to p62/SQSTM1 accumulation and Nuclear factor erythroid 2-Related Factor 2 (NRF2) up-regulation, preventing ROS increase induced by Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) and Interleukin-4 (IL-4).…”
Section: Hhv-6 Autophagy Dysregulation and Pathologiesmentioning
confidence: 99%
“…Dysregulating the activation of pathways involved in the autophagy induction, such as PKR/EIF2 alpha and mTOR, is another strategy put in place by other viruses belonging to the Herpesvirus family, such as Herpes Simplex virus-1 (HSV-1) or cytomegalovirus (HCMV) [31]. The latter, similarly to EBV, is able to promote the initial autophagic phases and inhibit the last ones, as its protein TRS1 interact with Beclin 1 [32]. As for HHV-6, EBV infection also reduces autophagy in infected monocytes, leading to p62/SQSTM1 accumulation and Nuclear factor erythroid 2-Related Factor 2 (NRF2) up-regulation, preventing ROS increase induced by Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF) and Interleukin-4 (IL-4).…”
Section: Hhv-6 Autophagy Dysregulation and Pathologiesmentioning
confidence: 99%
“…Indeed, autophagy is rapidly activated upon viral infections and contribute to viral sensing allowing a tight control of the infection. For example, the engagement of the Measle virus (Edmonston strain) cell surface receptor CD46 induces autophagy in the early step of infection via an indirect association with BECN1 and Herpesviruses are able to stimulate autophagy in the early steps of infection before inhibiting the autophagic maturation step to avoid their degradation (24)(25)(26). Nothing is currently known about the interplay between the autophagic machinery and HIV-1 during the early steps of CD4 TL infection but it has been demonstrated that the downregulation of several ATGs favors HIV-1 infection in these cells (27).…”
Section: Introductionmentioning
confidence: 99%